Pegaeophyton scapiflorum (J.D. Hooker & Thomson) C. Marquand & Airy Shaw subsp. scapiflorum (Cruciferae), a new record for Nepal flora - Shrestha, Mani R; Ghimire, Suresh K (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.112-113